2014
DOI: 10.1039/c4cy00757c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of fatty acids and triglycerides by Pt-loaded Nb2O5 catalysts

Abstract: Pt/Nb2O5 shows more than 60 times higher TON than non-SMSI Pt catalysts and previous catalysts for the hydrodeoxygenation of stearic acid to n-octadecane at 180 °C in 8 bar H2. Nb2O5 can act as an activation site of carbonyl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 43 publications
5
105
2
Order By: Relevance
“…This transformation is usually realized in more than one step involving the rate determining step. This is the reason for which in many cases carboxylic acids are used as probe molecules instead of plant oils or monoesters [92][93][94][95][96]. A detailed description of the SDO reaction pathways will be presented in a subsequent section, mainly with respect to the nickel based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This transformation is usually realized in more than one step involving the rate determining step. This is the reason for which in many cases carboxylic acids are used as probe molecules instead of plant oils or monoesters [92][93][94][95][96]. A detailed description of the SDO reaction pathways will be presented in a subsequent section, mainly with respect to the nickel based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these systems have some drawbacks such as decarbonylation and cracking as side reactions and the necessity of high catalyst loading or, in other words, low turnover numbers (TONs). In our previous study, we reported that Pt/Nb 2 O 5 showed a 60 times higher TON for hydrodeoxygenation of a fatty acid than Ni‐loaded Hβ zeolite and tungsten‐ or molybdenum‐based catalysts . Recently, we have developed Pt and MoO x co‐loaded on TiO 2 (Pt–MoO x /TiO 2 ) as a generally effective catalyst for the hydrogenation of amides, CO 2 , and sulfoxides .…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the catalysts containing sulphide Co(Ni)Mo phase [15][16][17][19][20][21][22][23][24] or noble metals [4,19,[25][26][27][28][29] were intensively investigated in HDO of the real feedstock and model compounds. Despite the high activity of noble metal catalysts, the high cost and shortage of noble metal restricted their practical application.…”
Section: Introductionmentioning
confidence: 99%